The Question of Grundentscheidung - O’Connell, Timothy E. (Philosophy & theology, 1997)
John Paul II’s encyclical Veritatis Splendor lists several objections to the theological concept of fundamental option. This article summarizes that concept, primarily as presented by Josef Fuchs. It then locates the concept, as Fuchs did, in the overarching theological anthropology of Karl Rahner, which is discussed at length. The objections of the encyclical are then engaged. In some cases, it is shown, the encyclical misunderstands fundamental option. In other cases, its rejection of the idea seems to entail rejection also of traditional Catholic doctrines. All this leads to concluding reflections in which fundamental option is evaluated in terms of its cogency, adequacy, usefulness, and necessity for a contemporary Christian anthropology.